What influences community positions towards nearby mining projects : eight cases from Brazil and Chile - Maher, Rajiv (Cranfield University, 2014)
This thesis looks at the influences and dynamics of community positions towards nearby mining projects in Brazil and Chile from an affected communities perspective. This subject is important because even after many initiatives and guidance aimed at helping companies to obtain good community relations, also known as a social license to operate (SLO), conflict in many mining community contexts is still prevalent today. In considering this, the thesis draws from Stakeholder, Resource Dependence and Social Movement Theories to help explain community positions towards these mining projects. The field research includes multiple stakeholder interviews from case studies of eight different mining affected communities in Brazil and Chile which are categorized into groups of higher or lower conflict. The main findings are that the more independent from mining a community is the greater the likelihood of conflict and the more independent type of communities perceived the mining projects as threats to their independence. The lower conflict communities were more economically dependent on their nearby mining projects. My findings also indicate that these more independent communities’ collective mobilization to resist such projects is nullified by influence strategies employed by mining companies via initiatives such as corporate social responsibility (CSR) that can serve as co-optation and lead to divisions within communities. The findings of this thesis call into question the validity of CSR-related notions such as an SLO from an affected communities perspective. An SLO implies community power; however, the research from the community perspective indicates that community power is not a constant or unchallenged. When countered by mining companies and the State, community resistance is broken down and community positions change. The scenario of mining company community relations set in a globalized world is dynamic and ever changing due to the various influences directed to and from affected mining communities. I propose a model which suggests that in situations of high interdependence between mining company and local community, stakeholder theory holds true. In these cases the vast array of social responsibility-related practical guidance literature on gaining good community relations is valid. Where a community is more independent and collectively resists the mining project, the company will use countermobilziation, CSR, co-optation and obstruction strategies to obtain a resistance free environment in which to conduct mining activity. The research contributes to stakeholder and resource dependence theories as well as to related practitioner literature on community relations and business and human rights by problematizing these theories and guidance. Specifically, the findings question the idea that CSR and best practice community relations lead to a win-win situation. In many cases implementing CSR exacerbates community conflict and divisions and is ultimately more irresponsible than responsible. The literature does not sufficiently consider the complexities of power imbalances between company/State and community in a globalized context and how this affects community relations and conflict from a community perspective. Further research should be conducted around the dynamics of influence strategies employed by State, company and community in the realm of development and human rights.